This Is My Body, My Body is Your Body, My Body Is the Body of the Word - Vidal, Lilou; Latimer, Quinn; Notéris, Emilie (Paris : Paraguay Press, 2019)
Asencio, Simon ; Baruchello, Gianfranco ; Binga, Tomaso ; Blank, Irma ; Boudry, Pauline ; Lorenz, Renate ; de Sousa, Ernesto ; Gonzalez-Torres, Felix ; Holmqvist, Karl ; Jarman, Derek ; La Rocca, Ketty ; Lippard, Hanne ; Matranga, Mélanie ; Pilgrim, Rory ; Rizzo, Michele
Ce livre est publié à l'occasion de l'exposition This Is My Body, My Body Is Your Body, My Body Is the Body of the Word, le Delta, Namur, 23 November 2019 - 19 avril 2020
boek